Painting a Community-Based Definition of Health: A Culture-Centered Approach to Listening to Rural Voice in Chaquizhca, Ecuador - Bates, Benjamin R.; Marvel, Diana L.; Nieto-Sanchez, Claudia; Grijalva, Mario J. (Frontiers in Communication, 2019)
The terms “health” and “well-being” are commonly used in health communication research. These terms, despite calls for a consensus definition, are rarely explicitly defined. We argue that, instead of imposing a universal definition of health or well-being, communities can be better served if we adopt a culture-centered approach and listen to their local, contextualized definitions of health. To demonstrate community articulation of a definition of health, we offer an analysis of wall art created by and with a community and our service and research team. After understanding a definition offered by a rural community in Chaquizca, Ecuador, we articulate how a community-based definition of health can become a way to culture-centered way to operationalize definitions offered by the World Health Organization in ways that better serve local communities.